Effect of VH–VL Families in Pertuzumab and Trastuzumab Recombinant Production, Her2 and FcγIIA Binding - Ling, Wei-Li; Lua, Wai-Heng; Poh, Jun-Jie; Yeo, Joshua Yi; Lane, David Philip; Gan, Samuel Ken-En (Frontiers in Immunology, 2018)
Many therapeutic antibodies are humanized from animal sources. In the humanization process, CDR grafting is tedious and highly prone to failure. With 7 known VH families, and up to 6 known κ VL families, there are choices aplenty. However, the functions of these families remain largely enigmatic. To study the role of these V-region families, we made 84 recombinant combinations of the various VH and VL family whole IgG1 variants of both Trastuzumab and Pertuzumab. We managed to purify 66 of these to investigate the biophysical characteristics: recombinant protein production, and both Her2 and FcγIIA binding. Our findings revealed combinations that showed improved recombinant antibody production and both antigen and receptor binding kinetics. These findings show the need to rethink antibodies as a whole protein, relooking at the functions of the antibody domains, and the need to include Ig receptor investigations for effective antibody therapeutics development.